Realization of RF Distance Bounding - Rasmussen, K; Čapkun, S (2010)
One of the main obstacles for the wider deployment of radio (RF) distance bounding is the lack of platforms that implement these protocols. We address this problem and we build a prototype system that demonstrates that radio distance bounding protocols can be implemented to match the strict processing that these protocols require. Our system implements a prover that is able to receive, process and transmit signals in less than 1ns. The security guarantee that a distance bounding protocol built on top of this system therefore provides is that a malicious prover can, at most, pretend to be about 15cm closer to the verifier than it really is. To enable such fast processing at the prover, we use specially implemented concatenation as the prover's processing function and show how it can be integrated into a distance bounding protocol. Finally, we show that functions such as XOR and the comparison function, that were used in a number of previously proposed distance bounding protocols, are not best suited for the implementation of radio distance bounding.